Phytochemical characterization, antihyperglycaemic and antihyperlipidemic activities of Setaria megaphylla in alloxan-induced diabetic rats - Jude E. Okokon; Koofreh Davies; Lekara John; Klinton Iwara; Wen-Wu Li; Paul S. Thomas (Elsevier, 2022)
Background: Setaria megaphylla (Steud) Dur & Schinz (Poaceae), a grass used ethnomedically by herbalists in Nigeria for the treatment of diabetes was evaluated for antidiabetic, hypolipidemic and pancreas protective potentials in rats. Methods: Solvents fractions (hexane, dichloromethane (DCM), ethyl acetate (EA) and methanol ) were investigated for antidiabetic, hypolipidemic and pancreas protective potentials in alloxan-induced diabetic rats. Glibenclamide was used as positive control. The fasting blood glucose (FBG) level, serum insulin, glycosylated hemoglobin (Hb1Ac), oral glucose tolerance test (OGTT) and lipids levels were determined. Histopathological study of the pancreas was done. Isolation of phytochemicals and their subsequent identification using Fourier transform infrared spectroscopy, gas chromatography-mass spectrometry and nuclear magnetic resonance spectroscopy were carried out. Results: Treatment of alloxan-induced diabetic rats with the leaf fractions caused significant (p < 0.05-0.001) reduction in FBG of treated diabetic rats in acute and prolonged studies as well as OGTT with DCM, EA and hexane fractions having pronounced activities. The leaf fractions also caused significant (p < 0.01) decreases in Hb1Ac levels and increases in serum insulin levels. The leaf fractions further caused lowering of serum total cholesterol, triglycerides, low density lipoprotein (LDL), very low density lipoprotein (VLDL) with increased high density lipoprotein (HDL) level in the treated diabetic rats. Histopathological study of pancreas revealed protective effect by the leaf fractions. 1-Triacontanal, 1-triacontanol, 1-dotriacontanol, 1-triacontyl cerotate, and stigmasterol were isolated and identified from the active DCM and EA fractions of this plant for the first time . Conclusion: The leaf fractions of S.megaphylla possess hypoglycemic, insulin secretion stimulatory, hypolipidemic, and pancreas protective potentials which may be due to the activities of the phytochemical constituents.